Experimental Investigation on the Aerodynamic Performance of Optimised Pedestrian Crash Friendly Sedan Front End Profiles - 1*V. Kausalyah, 1M.R Noor Ilya, 1I. Nur Azia, 2S. Shasthri , 1S.B.S. Baljit, V.; R Noor Ilya, M.; Nur Azia, I.; Shasthri, S.; B.S. Baljit, S. (International Journal of Engineering and Technology, 2018)
Aerodynamic characteristic is an important feature in the manufacturing of a vehicle regardless of its shape. Drag coefficient (Cd) values and vehicle profile shapes have been known to contribute in improving the aerodynamic characteristics. However, vehicles with good aerodynamic performance may not necessarily ensure the safety among pedestrians in the event of a frontal collision with the later. Thus, this research carries out an experimental work to determine the drag coefficient values for three different speeds, 50, 80 and 108 km/h. Three sedan vehicle models, which are optimized in the frontal profile for pedestrian crash are selected, based on previous research output and are modelled in CATIA V52016. These models are then fabricated with the scale of 1:20 through 3D printing method. The models are then set up separately in a wind tunnel having an open circuit suction with a 320mm Ã— 320mm Ã— 420 mm test section. Drag force and coefficient values are generated in the computer connected to the wind tunnel apparatus. Simulation is also simultaneously performed in ANSYS to compare against the experimental results. The drag coefficient values from the experiment fall in the range of 0.305-0.344, for the air velocity of 13.89 m/s, 0.332-0.353 for the velocity of 22.22 m/s and 0.310-0.394 for the velocity of 30 m/s. All the Cd values are very much within the permissible range for drag coefficient values ensuring that fuel efficiency and travel comfort are not compromised thus endorsing its aerodynamic performance.Â Â Â